Performance dashboards measuring, monitoring, and managing your business - Eckerson, Wayne W., 1958-; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2011)
"Tips, techniques, and trends on harnessing dashboard technology to optimize business performance In Performance Dashboards, Second Edition, author Wayne Eckerson explains what dashboards are, where they can be used, and why they are important to measuring and managing performance. As Director of Research for The Data Warehousing Institute, a worldwide association of business intelligence professionals, Eckerson interviewed dozens of organizations that have built various types of performance dashboards in different industries and lines of business. Their practical insights explore how you can effectively turbo-charge performance-management initiatives with dashboard technology. Includes all-new case studies, industry research, news chapters on "Architecting Performance Dashboards" and "Launching and Managing the Project" and updated information on designing KPIs, designing dashboard displays, integrating dashboards, and types of dashboards. Provides a solid foundation for understanding performance dashboards, business intelligence, and performance management. Addresses the next generation of performance dashboards, such as Mashboards and Visual Discovery tools, and including new techniques for designing dashboards and developing key performance indicators. Offers guidance on how to incorporate predictive analytics, what-if modeling, collaboration, and advanced visualization techniques. This updated book, which is 75% rewritten, provides a foundation for understanding performance dashboards, business intelligence, and performance management to optimize performance and accelerate results."--
pt. 1. The landscape for performance dashboards -- pt. 2. Performance dashboards in action -- pt. 3. Critical success factors : tips from the trenches.
Includes index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Management -- Evaluation; Organizational effectiveness -- Evaluation; Electronic books